2018
DOI: 10.1001/jamaneurol.2018.1058
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Guillain-Barré Syndrome With vs Without Zika Virus Infection, Puerto Rico, 2016

Abstract: The pathophysiologic mechanisms of Guillain-Barré syndrome (GBS) associated with Zika virus (ZIKV) infection may be indicated by differences in clinical features. OBJECTIVE To identify specific clinical features of GBS associated with ZIKV infection. DESIGN, SETTING, AND PARTICIPANTS During the ZIKV epidemic in Puerto Rico, prospective and retrospective strategies were used to identify patients with GBS who had neurologic illness onset in 2016 and were hospitalized at all 57 nonspecialized hospitals and 2 reha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 34 publications
4
71
1
1
Order By: Relevance
“…Taken together, the expression of myelin proteins across multiple ACE2 + TMPRSS2 + cells may hypothetically contribute to antigen presentation and autoimmune response in the context of viral infection. A small number of COVID-19 patients were reported to have Guillain-Barre Syndrome 144 , with a demyelinating process in some; this is consistent with observations of Guillain-Barre Syndrome following other viral infections such as Zika, influenza, and Epstein-Barr virus 139,145,146 . Whether anti myelin specific immunity can be induced by virus infected cells expressing myelin proteins remains an area for future study.…”
Section: Discussionsupporting
confidence: 81%
“…Taken together, the expression of myelin proteins across multiple ACE2 + TMPRSS2 + cells may hypothetically contribute to antigen presentation and autoimmune response in the context of viral infection. A small number of COVID-19 patients were reported to have Guillain-Barre Syndrome 144 , with a demyelinating process in some; this is consistent with observations of Guillain-Barre Syndrome following other viral infections such as Zika, influenza, and Epstein-Barr virus 139,145,146 . Whether anti myelin specific immunity can be induced by virus infected cells expressing myelin proteins remains an area for future study.…”
Section: Discussionsupporting
confidence: 81%
“…We reviewed 135 full-text articles, of which 31 were eligible for inclusion ( Fig 1). Of the 31 studies, 28 reported countryspecific GBS rates from 13 LAC countries (Tables 1 & 2), 3 regional rates, [18,35,36] 15 background rates [18,[35][36][37][38][39][40][41][42][43][44][45][46][47][48], 11 rates during an arboviral outbreak [49][50][51][52][53][54][55][56][57][58][59], and 5 compared rates before and during an outbreak [27,[60][61][62][63]. Many studies presented data from Brazil (29%) and Colombia (16%), and the majority (68%) were published in 2015 or later.…”
Section: Resultsmentioning
confidence: 99%
“…The IR in the French West Indies during the 2014 CHIKV epidemic was 3.45 per 100,000 persons [27], representing a two-fold increase from 1.77 per 100,000 during 2011-2013 (p = 0.006) [27]. [48,63]. In South America, there was substantial heterogeneity in the GBS IRs during the 2015 −2016 ZIKV epidemic for the population as a whole, ranging from 7.63 per 100,000 in Barranquilla, Colombia [58], to 0.71 per 100,000 in the Brazilian state of Piauí [54].…”
Section: Gbs and Arboviral Infectionsmentioning
confidence: 99%
“…Below we highlight a broad variety of clinical symptoms and outcomes associated with ZIKV infection, with the explicit purpose of identifying connectedness of ZIKV sequelae across different life stages. For in-depth comprehensive surveys focused on fetal or adult outcomes, we refer the reader to the following studies [9,19,20] .…”
Section: Zikv-mediated Pathogenesis?mentioning
confidence: 99%